Siwa Hot Springs as Reservoirs of Novel Antibacterials: Fosmid Library Construction and Screening - Abdoullateef, Basma M. T. S. (AUC Knowledge Fountain, 2026)
Antimicrobial resistance is a growing global health threat, further exacerbated by the emergence of multidrug-resistant bacterial strains. To address this pressing issue, there is an urgent need for the discovery of novel antimicrobial agents. A promising strategy is to explore previously untapped microbial communities for bioactive compounds. While much of the focus has been on well-studied environments, the hot springs of Siwa oasis in Egypt’s Western Desert—a popular tourist destination renowned for its therapeutic properties—remain largely unexplored in this context. Metagenomics offers a powerful tool for harnessing the vast microbial potential of such environments, facilitating the discovery of new biocatalysts and antimicrobial compounds. One effective functional metagenomic technique is fosmid library construction, which allows for the functional screening of microbial enzymes and the identification of bioactive compounds with antimicrobial activity. Environmental DNA was extracted from two hot springs, Cleopatra and Fatnas, located in Siwa Oasis, Egypt, to construct a metagenomic fosmid library. Water samples from both springs were first filtered through a serial filtration system. DNA was then extracted and used to build a fosmid library with the EpiFOS Fosmid Library Production Kit (Epicenter, Illumina, USA). In total, 6,151 clones were generated from the pooled environmental DNA samples of both springs. To identify potential antimicrobial compounds, the fosmid library was subjected to functional screening using an agar-based assay (the spot on lawn assay). This screening tested the clones against a range of bacterial strains, including both standard and clinically resistant Gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and Gram-negative (Acinetobacter baumannii and Klebsiella aerogenes) species. Two clones were identified that exhibited significant zones of inhibition against Acinetobacter baumannii and a Methicillin-Resistant Staphylococcus aureus (MRSA) strain. This study enabled the identification of antimicrobial compounds capable of targeting challenging bacteria, with the potential for development into pharmaceutical treatments to address emerging infectious threats.